Manufacture and characterisation of prototype straw bale insulation products. (30th November 2020) - Platt, Shawn; Maskell, Daniel; Walker, Pete; Laborel-Préneron, Aurélie
Highlights: Prototype wheat straw bales produced for use as a building insulation material. Computer Tomography used to investigate the internal structure of straw bales. Changing orientation of the stalks can improve thermal resistance by up to 28%. Abstract: This paper presents the development and characterisation of prototype wheat straw bales that have been produced specifically for use as a building insulation material. The use of straw bales still remains niche in the wider construction market. Whilst traditional straw bales can be used for either loadbearing or non-loadbearing applications, it is their thermal resistance that is of greatest benefit to building performance. There is great potential to significantly improve the thermal resistance and mechanical performance of straw bales for construction by reconfiguring the baling process to orientate the straws preferentially, and also produce bales sizes more suited for contemporary construction practices. Laboratory scale baling equipment has been developed to produce prototype bales with straws optimally orientated for thermal resistance. In a novel study Computer Tomography has been applied to investigate the internal structure and orientation of agricultural and prototype straw bales. The mechanical properties and thermal conductivity performance of novel straw bales are characterised. Changing orientation of the individual straws can improve thermal resistance by up to 28%, facilitating thinner walls, and enabling greater uptake of a novel low embodied carbon bio-based material into mainstream construction.